2013
DOI: 10.1007/s11356-013-2081-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation strategies and referencing trial of Scots and black pine populations subjected to heavy metal pollution

Abstract: The impact of industrial heavy metal pollution on Scots pine (Pinus sylvestris L.) and black pine (Pinus nigra Arn.) populations was investigated. Sampled pine stands, which were located in Upper Silesia (southern Poland) in an area strongly polluted by heavy metals, consisted of resistant and sensitive trees. To evaluate the adaptation process, genetic structure and diversity was tested using isozyme analysis. Higher levels of Zn, Pb, Cd and Cu were detected in needles of sensitive trees compared with resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…have been reported to exhibit a lower degree of genetic variation than metal-sensitive trees with respect to some isozyme loci (SHDH A, PGI, PGM, MDH C and DIA). This allele depletion suggests that genetic changes induced by heavy metals may dramatically affect the adaptation process in forest tree populations (Chudzinska et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…have been reported to exhibit a lower degree of genetic variation than metal-sensitive trees with respect to some isozyme loci (SHDH A, PGI, PGM, MDH C and DIA). This allele depletion suggests that genetic changes induced by heavy metals may dramatically affect the adaptation process in forest tree populations (Chudzinska et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Ewens-Watterson test for neutrality and the test of Vitalis et al (2001) confirmed that allele frequencies at locus GOT B, as well as GDH, MDH C, NDH and SHDH B, of P. nigra have been influenced by selection, acting either directly on this locus or on adjacent genomic regions. Among the analysed microsatellite loci of nuclear DNA, two (PtTX 4001 and SPAC 11.4) appeared to be under balancing selection (Chudzińska 2013). SSR markers showed lower or higher genetic diversity of sensitive and resistant subpopulations with respect to certain loci.…”
Section: Population Genetics: Heavy Metal Impactmentioning
confidence: 96%
“…Their number is higher under extreme conditions, e.g. in a pinе growing in a bog (Chudzińska 2013). The number of nuclеoli counted in silverstained interphase pine-seedling cells varied from 1 to 15 in data from Miasteczko Ś ląskie.…”
Section: Pinus Sylvestris: Cytology and Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), an endemic tree in Inner Mongolia including in Honghua'erji, is one of the main forestation species in temperate regions of China. Scots pine (P. sylvestris L.), a relative of Mongolia pine that is widespread from Western Europe to Eastern Siberia, is also an important tree in forestry (Krakau et al 2013) and is physiologically sensitive to environmental pollution (Chudzińska et al 2014), geographic weather variation (Oleksyn et al 2003) and climate change (Hurme et al 1997;Savolainen et al 2004). Studies have demonstrated that Scots pine and, by reasonable extension, Mongolia pine have broad, plastic adaptability in response to environmental heterogeneity, supporting the wide use of these trees in afforestation.…”
Section: Introductionmentioning
confidence: 99%